Metal nanoparticles as a therapeutic antibacterial agents in the era of antibiotics resistance: A review - layth hamid; Hanan Hamed (مجلة جامعة الانبار للعلوم الصرفة)
The increasing resistance of microorganisms to commonly used antibiotics has become a significant public health problem. To address this issue, new approaches are urgently needed to combating these types of pathogenic microbes. Nanoscience has led to the development of novel antibacterial materials including metal nanoparticles like silver, zinc, copper, gold, nickel, magnesium, iron, titanium, palladium selenium and aluminum. These materials have shown significant bactericidal properties against wide range of multi-drug resistant bacterial strains. Metal nanoparticles physically disrupt and inactivate various cellular contents of microorganisms without effected by resistance mechanisms. Nanomaterials small size, prolonged antibacterial effectiveness, and low toxicity contribute to reduce environmental hazards. However, scientists need to address several challenges, including health and bioethical concerns, risks of toxicity, and physiological and medical considerations associated with the use of nanomaterials as antibacterial drugs. Due to the lack of bacterial resistance mechanisms against nanoparticles, we could see these molecules replacing antibiotics in the treatment of pathogenic bacteria.